(untitled) (Redmond, Wash, 2003)
This volume provides detailed guidance for creating a deployment project plan, setting up a deployment test lab, creating software and hardware inventories choosing a licensing method and conducting a deployment pilot project
Keywords: Hệ điều hành (máy tính),Operating system ( computers)